Effect of SNEDDS (self-nanoemulsifying drug delivery system) kawista leaf aqueous extract (Limonia acidissima L.) on body and organ weight of Rats - Giriani Ayu Sabilla; Slamet Widiyanto (Bioscience, 2021)
SNEDDS (Self-Nanoemulsifying Drug Delivery System) is a pharmacological method that can increase the bioavailability of a drug. Kawista leaf aqueous extract contains secondary metabolites in the form of flavonoids, tannins, and saponins. SNEDDS preparation of kawista leaf aqueous extract has not been reported on its effect on body weight and organs of rats. The purpose of this study was to determine the effect of SNEDDS preparation of kawista leaf aqueous extract on body weight, liver and kidney weight of Rattus norvegicus in acute toxicity testing using the OECD 423 method. Data on body weight and organ weight of the liver and kidneys of female white rats of the Wistar strain were obtained during toxicity testing by acute OECD method 423. In this test, rats were divided into 3 treatment groups,namely control, SNEDDS, and SNEDDS of kawista leaf aqueous extract, with a total of 5 rats per treatment. The test was carried out in 2 terms of dosing according to OECD 423, wherein the second term the amount of the dose given was determined from the data on the response of the test animals to the dosage of the preparations in the first term. The results were analyzed using One Way ANOVA followed with Duncan. The results showed that the SNEDDS preparation of kawista leaf aqueous extract did not affect the body weight or the weight of the liver and kidneys of rats which was indicated from the statistical test results that there was no significant difference between treatments. This study conclude that SNEDDS preparation of kawista leaf aqueous extract did not affect the body weight or liver and kidney organs of rats.SNEDDS (Self-Nano Emulsifying Drug Delivery System) merupakan metode  yang dapat meningkatkan bioavailabilitas suatu obat. Ekstrak air daun kawista mengandung metabolit sekunder berupa flavonoid, tanin, dan saponin. Sediaan SNEDDS ekstrak air daun kawista belum dilaporkan pengaruhnya terhadap berat badan dan organ tubuh tikus. Tujuan penelitian ini adalah untuk mengetahui pengaruh sediaan SNEDDS ekstrak air daun kawista terhadap bobot badan, bobot hati dan bobot ginjal Rattus norvegicus pada uji toksisitas akut menggunakan metode OECD 423. Data bobot badan dan bobot organ hati dan ginjal tikus putih betina galur Wistar diperoleh selama pengujian toksisitas dengan metode OECD akut 423. Pada pengujian ini tikus dibagi menjadi 3 kelompok perlakuan yaitu kontrol, SNEDDS, dan SNEDDS ekstrak air daun kawista, dengan jumlah tikus per perlakuan sebanyak 5 ekor. Pengujian dilakukan dalam 2  dosis menurut OECD 423, dimana  jumlah dosis kedua yang diberikan ditentukan dari data respon hewan uji terhadap dosis pertama. Hasil dianalisis menggunakan One Way ANOVA dilanjutkan dengan Duncan. Hasil penelitian menunjukkan bahwa sediaan SNEDDS ekstrak air daun kawista tidak berpengaruh terhadap bobot badan atau bobot hati dan ginjal tikus yang ditunjukkan dari hasil uji statistik tidak terdapat perbedaan bermakna antar perlakuan. Penelitian ini menyimpulkan bahwa sediaan SNEDDS ekstrak air daun kawista tidak berpengaruh terhadap bobot badan, hati dan ginjal tikus.